Pay for Play How the Music Industry Works, Where the Money Goes, and Why - Wayte, Larry (Open textbook library., 2023)
The history of music is closely linked to the history of copyright law. This book explores how the law shaped music and the music industry. From church and court patronage in pre-19th Century Europe, to the effects of social media on music, this book explores the abiding influence of the law on music.